Determination of machine‐specific tolerances using statistical process control analysis of long‐term uniform scanning proton machine QA results. Issue 9 (1st August 2020) - Rana, Suresh; Eckert, Colton; Singh, Hardev; Zheng, Yuanshui; Chacko, Michael; Storey, Mark; Chang, John
Abstract: Purpose: The purpose of this study was twofold: (a) report the long‐term monthly quality assurance (QA) dosimetry results of the uniform scanning beam delivery system, and (b) derive the machine‐specific tolerances based on the statistic process control (SPC) methodology and compare them against the AAPM TG224 recommended tolerances. Methods: The Oklahoma Proton Center has four treatment rooms (TR1, TR2, TR3, and TR4) with a cyclotron and a universal nozzle. Monthly QA dosimetry results of four treatment rooms over a period of 6 yr (Feb 2014–Jan 2020) were retrieved from the QA database. The dosimetry parameters included dose output, range, flatness, and symmetry. The monthly QA results were analyzed using the SPC method, which included individuals and moving range (I‐MR) chart. The upper control limit (UCL) and lower control limit (LCL) were set at 3σ above and below the mean value, respectively. Results: The mean difference in dose output was −0.3% (2σ = ±0.9% and 3σ = ±1.3%) in TR1, 0% (2σ = ±1.4% and 3σ = ±2.1%) in TR2, −0.2% (2σ = ±1.0% and 3σ = ±1.6%) in TR3, and −0.5% (2σ = ±0.9% and 3σ = ±1.3%) in TR4. The mean flatness and symmetry differences of all beams among the four treatment rooms were within ±1.0%. The 3σ for the flatness difference ranged from ±0.5% to ±1.2%. The 3σ for the symmetry difference ranged from ±0.4% to ±1.4%. The SPC analysis showed that the 3σ for range 10 cm (R10), R16, and R22 were within ±1 mm, whereas the 3σ for R28 exceeded ±1 mm in two rooms (3σ = ±1.9 mm in TR2 and 3σ = ±1.3 mm in TR3). Conclusion: The 3σ of the dose output, flatness, and symmetry differences in all four rooms were comparable to the TG224 tolerance (±2%). For the uniform scanning system, if the measured range is compared against the requested range, it may not always be possible to achieve the range difference within ±1 mm (TG224) for all the ranges.